A Legal Analysis of the Handling of Theft Criminal Investigations and the Implementation of Restorative Justice in an Effort to Formulate an Ideal Justice System in Batam City - Muhammad Brata Ul-Husna; Andri Winjaya Laksana (UNISSULA Semarang, 2025)
Abstract. In the preamble to the 1945 Constitution, paragraph 4, it is emphasized that the national goal of the State of Indonesia is to protect all Indonesian people and all of Indonesia's homeland and to advance general welfare, to educate the nation's life and to participate in implementing world order based on independence, eternal peace and social justice. The implementation of the national goal in order to realize the noble ideals of the Indonesian nation towards a just and prosperous society based on Pancasila and the 1945 Constitution, is realized through the existence of a national development program. Indonesia is a state of law. The affirmation of Article 1 paragraph (1) of the 1945 Constitution is that the state guarantees every Indonesian citizen equal standing before the law. This is regulated in Article 27 Paragraph (1) of the 1945 Constitution which reads: